The surrogate : a novel - Halleen, Toni (Harper, an imprint of HarperCollinsPublishers, 2021)
When surrogate mother, Cally has a change of heart, engineering a harrowing escape from the hospital with the newborn, a whole series of doubts and secrets are revealed and it's no longer clear what's "right" and what's "wrong."